2016
DOI: 10.32368/fjes.20161205
|View full text |Cite
|
Sign up to set email alerts
|

Households Study on Out-of-Pocket Health Expenditures in Pakistan

Abstract: Public Health expenditure to GDP ratio has remained low in developing countries and general public has no choice but to seek healthcare from their own pocket, which has remained the dominant source of financing. In Pakistan, out of pocket expenditures are around 70% of the total health expenditures. The study analyzed the out of pocket health expenditure patterns of Pakistan historically, across provinces, rural and urban areas. Further it compares between below poverty line and above poverty line households w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In Pakistan, OOP expenditures are around 70% of the total healthcare expenditures. Not only are CVDs the most prevalent diseases among South Asian population, but also being a South Asian is considered a risk factor for CVD ( Lozano et al, 2012 ; Khalid and Sattar, 2016 ). In this context, our data suggested that probably many CVD patients, especially living in poverty struck rural areas, had to forego the treatments, considering the extent of unaffordability of CVD medicines observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan, OOP expenditures are around 70% of the total healthcare expenditures. Not only are CVDs the most prevalent diseases among South Asian population, but also being a South Asian is considered a risk factor for CVD ( Lozano et al, 2012 ; Khalid and Sattar, 2016 ). In this context, our data suggested that probably many CVD patients, especially living in poverty struck rural areas, had to forego the treatments, considering the extent of unaffordability of CVD medicines observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Public health expenditure to GDP ratio has remained low in developing countries and the general public has no choice but to seek healthcare from their own pocket, which has remained the dominant source of financing. [3] Significant Out of pocket expenditure may lead households to a "financial catastrophe" in the absence of risk and payment pooling mechanisms or insurance. [4] Globally, approximately 44 million households or more than 150 million individuals face cata-strophic health expenditure (CHE), and about 25 million households or more than 100 million individuals are pushed into poverty by the need to pay for services every year.…”
Section: Introductionmentioning
confidence: 99%
“…17 Health expenditure to gross domestic product (GDP) ratio has always remained low in Pakistan and maintained less than one percent of the total GDP. 18 According to The World Bank, out-ofpocket expenditure (percentage of current health expenditure) is 65.23 %. Another study conducted in Lahore may also be related to our study which showed that most of the patients managed to receive their treatments in public hospitals and none of them was health insured.…”
Section: Discussionmentioning
confidence: 99%